Synthesis and Crystal Structure of 3-Amino-1-(5-Chloro-2-Hydroxyphenyl)Imidazolidine-2,4-Dione - Aydin, Abdullah; Onkol, Tijen; Akkurt, Mehmet; Büyükgüngör, Orhan; Sahin, M. Fethi (Informa UK Limited, 2013)
The present study describes the synthesis, spectral data, and single crystal X-ray structural analysis of 3-amino-1-(5-chloro-2-hydroxyphenyl)imidazolidine-2,4-dione. X-Ray analysis revealed that the title compound did not have the anticipated structure, but had that of a different substance. This unexpected conformation generated the interest in studying the synthesis of this compound. The inspected compound, 3-amino-1-(5-chloro-2-hydroxyphenyl)imidazolidine-2,4-dione, is a pharmaceutical intermediate and is nonplanar. Its benzene and five-membered rings have a dihedral angle of 53.95(7)°. The conformation is stabilized by intermolecular O‒H … O, O‒H … N, and N‒H … O interactions and a weak C‒H … π interaction.
Keywords: X-ray; synthesis; structure; dione; amino